Impact Of Tourism Visits On Increasing Income Of UMKM Actors In Attraction Objects Tourism (ODTW) Hunimua-Liang Beach Central Maluku District. - Muddin Wael; A. L. O. Kakisina; A. E. Pattiselanno (Utan Kayu Publishing, 2024)
The research aims to determine the impact of tourist visits on increasing the income of business actors at the Hunimua-Liang Beach tourist attraction (ODTW), Central Maluku Regency. Respondent sampling was carried out using the purposive sampling method using qualitative analysis. These results indicate that the level of tourist visits at Hunimua-Liang Beach on weekdays and long holidays is not too busy. In contrast to the level of tourist visits on weekends, there are always lots of tourists who usually visit, usually mostly local tourists, there are also domestic and foreign tourists but not too many. The income of traders at Hunimua-Liang Beach on weekdays and long holidays is not very large because there are not too many tourists who come to visit so they don't sell much. In contrast to the income obtained on weekends, the income obtained is greater because many tourists come to visit and many people buy what they sell.